2005
DOI: 10.1186/1471-2407-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Half versus full vacuum suction drainage after modified radical mastectomy for breast cancer- a prospective randomized clinical trial[ISRCTN24484328]

Abstract: Background: Suction drains are routinely used after modified radical mastectomy and are an important factor contributing to increased hospital stay as the patients are often discharged only after their removal. Amongst various factors that influence the amount of postoperative drainage, the negative suction pressure applied to the drain has been reported to be of great significance. While a high negative suction pressure is expected to drain the collection and reduce the dead space promptly, it may also preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 10 publications
2
56
1
1
Order By: Relevance
“…Subcutaneous indwelling closed-suction drainage has been used in other types of surgery including breast and thyroid [9,39]. We have used the subcutaneous indwelling method for 3 years and have noted no particular problems with blood loss or wound complications.…”
Section: Introductionmentioning
confidence: 99%
“…Subcutaneous indwelling closed-suction drainage has been used in other types of surgery including breast and thyroid [9,39]. We have used the subcutaneous indwelling method for 3 years and have noted no particular problems with blood loss or wound complications.…”
Section: Introductionmentioning
confidence: 99%
“…It is also recommended to stay below the superior most IBN in order not to interfere with the lymphatic drainage of the upper extremity. Keeping dissection below the superior most IBN has been observed in various studies to be associated with lower incidence of upper limb lymphedema [4][5][6]. If one decides to sacrifice the intercostobrachial nerves, it is recommended that a cold knife rather than diathermy should be used to prevent postoperative neuralgia (Fig.…”
Section: Commandment-7-intercosto-brachial Nerves (Ibn)mentioning
confidence: 99%
“…14) After a thorough saline wash, the wound is closed after leaving two suction drains (or only one) in situ, one each for the axilla and flaps. The author in a randomized controlled study (ISRCT N number-24484328) observed that the seroma rates are lower with the use of half suction rather than full suction drains [6]. Fig.…”
Section: Commandment-8-reaching the Lateral And Lower Limit Of Axillamentioning
confidence: 99%
See 1 more Smart Citation
“…The survival drops by nearly 50% in patients with positive axillae. The "gold standard" method of assessing the axilla is to establish the histological evidence of disease in the nodes, making assessment of axilla mandatory even in node negative patients [1][2][3].…”
mentioning
confidence: 99%